Does irisin has neuroprotective effect against diabetes induced neuropathy in male rats? - Kalkan, Omer Faruk; Aktas, Osman; Surmeneli, Yunus Emre; Alver, Ahmet; Ozcan, Mete; Sahin, Zafer (Taylor & Francis Ltd, 2023)
We aimed to investigate the contribution of irisin in the neuroprotective process of exercise training in diabetic rats. Serum irisin levels, thermal and mechanical pain thresholds and intracellular calcium ([Ca2+](i)) levels in sensory neurons were measured at different time intervals during the eight weeks of exercise sessions for the control, non-exercise diabetics (3 groups) and exercise performing (low and high intensity groups) diabetic rats (n = 7-10 for all groups). Non-exercise diabetic groups were treated with irisin in different doses (1, 10 and 20 mu g/kg respectively). Recovered pain thresholds at the end of the exercise sessions (p < .05), higher serum irisin levels that compared to control and diabetics (p < .05) and insignificant mean [Ca2(+)](i) peak amplitudes in sensory neurons (p > .05) obtained from experiments. Furthermore, irisin injection decreased the thermal pain threshold of diabetics only at 60th minutes (p < .05). Irisin may have a role in the neuroprotective effect of exercise training.
Keywords: Exercise; irisin; neurodegeneration; neuropathic pain; calcium